Critical Success Factors for Business Intelligence Implementation in an Enterprise Resource Planning System Environment Using DEMATEL: A Case Study at a Cement Manufacture Company in Indonesia - Ridha Adjie Eryadi; Achmad Nizar Hidayanto (Journal of Information Technology Management)
This paper is aimed at evaluating critical success factors in Business Intelligence (BI) implementation in an Enterprise Resource Planning (ERP) environment. The data analysis method used in this paper is the Decision Making Trial and Evaluation Laboratory Model (DEMATEL). The study has been conducted on a cement manufacturing strategic holding company that has implemented ERP since 2010. This research is done through literature review and interviews with the head of the BI development team as the expert for this research, before distributing questionnaires to Information and Communication Technologies (ICT) Team and BI stakeholders. The questionnaire has been addressed to 18 respondents consisting of the BI development team and stakeholders, which include the Strategic Planning Division, Business Development Division, Transformation Management Division, and Accounting Division. There are 13 factors evaluated, consisting of 4 factors related to the organization, four factors related to the development process, three factors related to the technology, and two factors associated with the external environment. The most critical factor for organizational criteria is Top management support. The most important factor for process criteria is Effective project management. The most important factor for technology criteria is System reliability, flexibility, and scalability. The most important factor for environment criteria is the selection of a vendor.